Medical Record Laboratory Electronic Information System Design Analysis - Ayu Wijaya; Andi Muh.Adam Aminuddin; Nelly Nugrawati (YCMM, 2022)
This study aims to create a system design information record medical electronic where is the recording system medical electronic is system that provides information completeness of patient data and record medical During maintenance and storage all patient data. System management Archives in the Amanah Stikes Laboratory Record Medical not yet computerized. Patient data entry still uses paper, while recording and storage record medical done manually. Study this aim for making related apps with system information record medical electronic on Amanah Stikes laboratory. In research descriptive this we use approach qualitative, what d do on guarantor answer laboratory staff record medical. Based on from result study with doing questionnaire and observation, therefore then Relevant data is required with recording record medical take care road for example number record medical information, patient data info, and disease data info, in designing a system information record medical electronics.